Corporate governance and firm performance - Bhagat, Sanjai; Bolton, Brian (Journal of Corporate Finance, 2008)
How is corporate governance measured? What is the relationship between corporate governance and performance? This paper sheds light on these questions while taking into account the endogeneity of the relationships among corporate governance, corporate performance, corporate capital structure, and corporate ownership structure. We make three additional contributions to the literature: First, we find that better governance as measured by the Gompers, Ishii, and Metrick [Gompers, P.A., Ishii, J.L., and Metrick, A., 2003, Corporate governance and equity prices, Quarterly Journal of Economics 118(1), 107–155.] and Bebchuk, Cohen and Ferrell [Bebchuk, L., Cohen, A., and Ferrell, A., 2004, What matters in corporate governance?, Working paper, Harvard Law School] indices, stock ownership of board members, and CEO-Chair separation is significantly positively correlated with better contemporaneous and subsequent operating performance. Second, contrary to claims in GIM and BCF, none of the governance measures are correlated with future stock market performance. In several instances inferences regarding the (stock market) performance and governance relationship do depend on whether or not one takes into account the endogenous nature of the relationship between governance and (stock market) performance. Third, given poor firm performance, the probability of disciplinary management turnover is positively correlated with stock ownership of board members, and board independence. However, better governed firms as measured by the GIM and BCF indices are less likely to experience disciplinary management turnover in spite of their poor performance.